2023
DOI: 10.3390/nu15030756
|View full text |Cite
|
Sign up to set email alerts
|

Chrononutrition during Pregnancy and Its Association with Maternal and Offspring Outcomes: A Systematic Review and Meta-Analysis of Ramadan and Non-Ramadan Studies

Abstract: Much evidence suggests that food intakes and eating patterns are major determinants of the phase of peripheral circadian clocks, and desynchronization between them is thought to contribute to the development of metabolic disorders. However, much remains to be understood about how different dimensions of chrononutrition during pregnancy affect pregnant women’s and their offspring’s health outcomes. Therefore, we systematically reviewed and integrated all emerging evidence on chrononutrition during pregnancy (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…A broader set of studies have assessed Ramadan fasting and perinatal outcomes, but this type of practice differs from a non-religious habitual dietary behavior. A recent meta-analysis showed that Ramadan-related fasting affected lower GWG during fasting but did not affect weight gain throughout pregnancy, gestational age at birth, preterm birth, birthweight, low birthweight, or other maternal-infant outcomes ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…A broader set of studies have assessed Ramadan fasting and perinatal outcomes, but this type of practice differs from a non-religious habitual dietary behavior. A recent meta-analysis showed that Ramadan-related fasting affected lower GWG during fasting but did not affect weight gain throughout pregnancy, gestational age at birth, preterm birth, birthweight, low birthweight, or other maternal-infant outcomes ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…26 The timing of eating has been associated with various health outcomes, and previous research has also correlated it with gestational parameters such as gestational weight gain, [27][28][29] gestational diabetes, 30,31 and fetal growth. 32,33 It is inferred that the timing of maternal food intake has the potential to influence maternal and fetal circadian rhythms, fetal development during pregnancy, and the subsequent metabolic health of the offspring, [34][35][36] though this is still not fully understood. Previous studies conducted with pregnant women in our group have shown that pregnant women who tend to be evening chronotype consume breakfast later in the day, have poorer dietary patterns concerning total fruit intake, 37 have a higher energy and carbohydrate consumption at night, and exhibit a worse pattern of gestational weight gain in the third trimester (T), 38 as well as a higher likelihood of gaining weight early in the gestational period.…”
Section: Introductionmentioning
confidence: 99%
“…During pregnancy, the deterioration of sleep and the occurrence of insomnia (3,4,7) are compounded by hormonal changes, such as increased progesterone levels and leptin resistance (23) , which can lead to heightened appetite and increased food consumption (24) . Moreover, poor sleep during pregnancy can impact chrononutrition patterns through associations between sleep and food consumption (25)(26)(27) . Recent studies involving pregnant women and chrononutrition, which explore the relationship between the circadian clock, metabolic physiology and nutrition (25,26) , have demonstrated that eating during times that go against the body's natural circadian rhythms, such as the inactive/sleep phase, negatively affects nocturnal metabolism, resulting in worsened glycaemic, insulinemic and lipidemic responses, as well as greater weight gain (25)(26)(27)(28) .…”
mentioning
confidence: 99%